Growth Response of Cymbidium Orchid Subcultures Due to the Treatment of Ms Media Concentration and Foliar Fertilizer in Vitro - Arbi, Dwiki Prahdano; Nilahayati, Nilahayati; Nazirah, Laila; Handayani, Rd. Selvy; Hafifah, Hafifah (Yayasan Pertanian Tropika Indonesia (YPTI), 2021)
Orchids are very popular in Indonesia and the world as ornamental plants and floral arrangements. Therefore, orchids should be maintained and cultivated as they have high economic value. Orchids can be propagated by using seeds. Orchid seeds are tiny and do not have endosperm, making growing difficult. Efforts can be made to propagate this plant by using tissue culture methods. This study was conducted to determine the effect of MS media concentration and foliar fertilizer on the growth of Cymbidium orchid subcultures in vitro. The research method used a factorial randomized block design (RBD) of two factors. The first factor is the MS media concentration with three levels, which are M0 (full of MS), M1 (Â½ of MS), and M2 (Â¼ of MS). The second factor is the concentration of foliar fertilizer, which consists of three levels: P0 (0 g/L), P1 (1 g/L), and P2 (2 g/L).